Statutory adjudication : a practical guide - Simmonds, Derek (Oxford, UK ; Malden, MA : Blackwell Pub., 2003)
No one in the business of adjudication should be without it' Arbitration, February 2004.
Preface; Abbreviations; PART 1 An Introduction to Adjudication; PART 2 So You Want To Go To Adjudication?; PART 3 So You Are Being Taken To Adjudication; PART 4 Matters of Common Interest; PART 5 Statutory Payment Requirements; Index.
Includes index.
Print version record.
John Wiley and Sons
Keywords: Great Britain; Housing Grants, Construction and Regeneration Act 1996 (Great Britain); Construction contracts -- Great Britain; Arbitration and award -- Great Britain; Dispute resolution (Law) -- Great Britain; z; Arbitrage (Droit) -- Grande-Bretagne.; Arbitration and award; Construction contracts; Dispute resolution (Law); Great Britain